ChemInform Abstract: Flow Chemistry Syntheses of Styrenes, Unsymmetrical Stilbenes and Branched Aldehydes. Issue 23 (16th May 2013) - Bourne, Samuel L.; O'Brien, Matthew; Kasinathan, Sivarajan; Koos, Peter; Tolstoy, Paeivi; Hu, Dennis X.; Bates, Roderick W.; Martin, Benjamin; Schenkel, Berthold; Ley, Steven V.
Abstract The flow reactions for vinylation and hydroformylation can be operated in sequence to yield arylethyl carbaldehydes from aryl iodides.